Heavy Metal Content of Pb and Cu in Wideng Crab (Episesarma sp.) - Saraswati, Suprabadevi Ayumayasari; Suryaningtyas, Endang Wulandari; Wijayanti, Ni Putu Putri (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 1 (2022): ATBES, 2022)
The Morosari estuary area is an estuary area consisting of aquaculture areas, mangrove areas, tourist areas, and several large-scale industrial and household activities. This situation causes the entry of waste containing heavy metals (Pb and Cu) into the estuary area. Wideng crab (Episesarma sp.) is one of the biotas that lives in the area and is influenced by the presence of heavy metals (Pb and Cu). This study aims to determine the content of heavy metals Pb and Cu in the mouth of the Morosari River and in the meat of the Wideng Crab (Episesarma sp.). The research was conducted in April – June 2009 and located at the mouth of the Morosari River (Demak). The research method used is a descriptive exploratory method, while sampling using purposive random sampling was conducted at 3 stations. A sampling of Wideng Crabmeat (Episesarma sp.), water, and sediment was carried out every 2 weeks as many as 5 samples and continued with analysis at the Central Laboratory of Kopertis Growth Region IV Semarang. Furthermore, the data obtained were analyzed descriptively. The results of the analysis of the Pb content in water were 0.039 - 0.089 mg/l, and the content in crab meat was 0.175 - 0.335 mg/kg. While the content of Cu in water is 0.024 - 0.055 mg/l, and in crab meat 0.032 - 0.16 mg/kg. The value of heavy metal content in the water has exceeded the quality standard threshold allowed by the Ministry of Environment Number 51 of 2004